Isolation, Characterization and Biofilm inhibition of Pyocyanin pigment extracted from Pseudomonas aeruginosa - Challaraj Emmanuel E.S., Madonna John, SiyamFathima (International Journal of Advanced Science and Technology, 2020)
Pseudomonas aeruginosa produce the pigment pyocyanin, which is a secondary metabolite and has antibiotic activity. Pyocyanin is a blue-green pigment that is produced by P. aeruginosa in a media that is devoid of iron content. Pyocyanin producing Pseudomonas aerginosa was isolated from soil sample. Pyocyanin was extracted and purified using chloroform and then characterized using TLC, UV-Vis and FTIR scpectroscopy. The Rf value was found to be 0.79. The UV-Vis Spectrum showed a maximum peak at 277 nm. Pyocyanin has a high antimicrobial activity and can act as a broad-spectrum antibiotic. The inhibition concentrations were found to be as low as 5μg/ml. The extracted pyocyanin showed antibacterial and anti-biofilm activities.